(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the interaction between primary and derivative logical meanings in language, focusing on how semantic shifts occur through contextual usage and cognitive interpretation. It analyzes the processes by which words develop secondary meanings while retaining their original semantic core. Special attention is given to the mechanisms of metaphorization, metonymy, and semantic extension that contribute to meaning transformation in discourse. The study highlights that primary meanings provide the foundation for lexical semantics, while derivative meanings emerge through pragmatic and contextual factors. The findings demonstrate that the interaction between these two types of meaning is dynamic and essential for the flexibility and expressiveness of language.